What is the nature of peer interactions in children with language disorders? A qualitative study of parent and practitioner views. (March 2021) - Lloyd-Esenkaya, Vanessa; Forrest, Claire L; Jordan, Abbie; Russell, Ailsa J; Clair, Michelle C St
Background and aims: Children with Language Disorders (LDs) can exhibit increased levels of social withdrawal, aggression and problems managing social conflicts. The reasons underlying this pattern of social interaction profiles remain unclear. This qualitative study aimed to document the nature of social interactions between children with LDs and their peers, and to evaluate explanations for their social behaviour, as understood by parents and practitioners. Methods: This study focused on children with LDs who spend school hours with other children with LDs. Three parent focus groups (n = 8) and three practitioner focus groups (n = 10) were conducted with parents of children aged 4–12 attending specialist language schools and practitioners working at these schools. This was a mixed clinical sample. All children of participating parents had LD as their primary area of need, which was the reason they required specialist schooling. Focus groups were conducted across two specialist schools in the UK between March and June 2018. Results: An inductive reflective thematic analysis of the data identified three themes; social knowledge, coping strategies, and emotional competence. Parents and school staff reported that children with LDs experience difficulties managing peer interactions due to a combination of challenges including difficulties with understanding and regulating emotions, and difficulties understanding social situations. Some of the children with LDs were described as having developed strategies to cope with their challenges, for example imposing structure on their social interactions to manage uncertainty, which has implications for their social interactions with peers. Conclusions: Children with LDs have difficulties understanding emotions, difficulties understanding their peer's intentions and difficulties resolving conflict situations independently according to their parents and practitioners working with these children. Participants proposed a novel explanation that social withdrawal may be used adaptively by children with LDs to process information. This study demonstrates the complexity of the relationship between Language Disorders and peer interaction profiles. Implications: Suggestions are offered regarding future research directions, such as investigating the specific contribution language skills make to children's emotion understanding, to better understand the reasons for peer interaction difficulties in children with Language Disorders.